Modelling forward osmosis-nanofiltration integrated process for treatment and recirculation of leather industry wastewater. (4th August 2019) - Pal, Parimal; Sardar, Moumita; Pal, Madhubonti; Chakrabortty, Sankha; Nayak, Jayato
Highlights: Modelling of a FONF system done for tannery wastewater treatment. Unique orientation of the FO membrane reduces concentration polarization significantly. Flat-sheet cross flow membrane module offers largely fouling-free service. Donnan, steric and dielectric exclusion of ions considered in the model. The model successfully predicted performance of the integrated FONF process. Abstract: Modelling of a forward osmosis-nanofiltration (FONF) integrated treatment system for treating hazardous wastewater has been done with model validation against experimental data of a semi-pilot unit using live wastewater from a leather industry. The flat sheet cross flow forward osmosis (FO) membrane module ensured near 100% rejection of chromium while total pollution load of the wastewater in terms of chemical oxygen demand (COD), chlorides and sulphates came down by 98% . A reasonably high water flux of about 48 L/m 2  h (LMH) could be sustained in the FO module. The coupled downstream NF system recovered the draw solute NaCl by more than 98% for recycling in the FO loop. That the developed model is capable of predicting system performance quite accurately is reflected in low relative error (<0.1), high overall correlation coefficient (R 2  > 0.98) and high Wilmot d-index (>0.95). The model will help assess operating conditions, system design and hence industrial scale up.